Measurement Methods to Detect, Characterize, and Quantify Engineered Nanomaterials in Foods. Issue 4 (July 2014) - Singh, Gurmit; Stephan, Chady; Westerhoff, Paul; Carlander, David; Duncan, Timothy V.
Abstract This article is one of a series of 4 that reports on a task of the NanoRelease Food Additive project of the International Life Science Institute Center for Risk Science Innovation and Application to identify, evaluate, and develop methods that are needed to confidently detect, characterize, and quantify intentionally produced engineered nanomaterials (ENMs) released from food along the alimentary tract. This particular article focuses on the problem of detecting ENMs in food, paying special attention to matrix interferences and how to deal with them. In this review, an in‐depth analysis of the literature related to detection of ENMs in complex matrices is presented. The literature review includes discussions of sampling methods, such as centrifugation and ENM extraction. Available analytical methods, as well as emerging methods, are also presented. The article concludes with a summary of findings and an overview of potential knowledge gaps and targets for method development in this area.